Effectiveness and safety of acupotomy for lumbar disc herniation: a study protocol for a randomized, assessor-blinded, controlled pilot trial - Eunseok Kim; So Yun Kim; Hye Su Kim; Jeong Kyo Jeong; So-Young Jung; Chang-Hyun Han; Young-Il Kim (Integrative Medicine Research)
Background: Acupotomy aims to reduce pressure on the nerve, improve surrounding blood circulation, and recover the kinetic state of soft tissue in treating lumbar disc herniation. Although several previous studies have suggested the potential use and substantial benefits of acupotomy, there is still insufficient evidence regarding this technique. This trial is designed to determine if acupotomy is more effective than manual acupuncture in improving low back pain and/or leg pain, disability, lumbar mobility, and quality of life in patients with herniated lumbar disc. Methods: Fifty eligible patients will be randomly assigned to an acupotomy group or a manual acupuncture group in a 1:1 ratio. The experimental group will receive acupotomy at the affected side’s inner core muscles and soft tissue at the level of the herniated disc where tenderness appears (twice per week for 2 weeks). The control group will receive manual acupuncture (thrice per week for 2 weeks) at GV3 (Yaoyangguan) and the bilateral BL23 (Shenshu), BL24 (Qihaishu), BL25 (Dachangshu), and BL26 (guanyuanshu) for local points and the bilateral GB30 (Huantio), BL40 (Weizhong), and BL60 (Kunlun) for distant points. The primary outcome will be the mean change in the visual analog scale from baseline to 4 weeks (2 weeks after final treatment). The Oswestry Disability Index, Modified-Modified Schober Test, and EuroQol five dimensions questionnaire will determine secondary outcomes. Adverse events will be evaluated at every visit. Discussion: This study will provide valuable data and insights for a confirmative, full-scale randomized controlled trial to determine the clinical effects of acupotomy.